Peran Apoteker dalam Pengelolaan Penyakit Degeneratif di Dusun Mergan Sendangmulyo, Sleman, D.I. Yogyakarya - Dita Maria Virginia; Aris Widayati (Universitas Sanata Dharma, 2018)
Findings of the preliminary survey showed a high proportion of geriatric people in Dusun Mergan, Sendangmulyo, Sleman, which leads to high risk of cardiovascular and other degenerative diseases. This community service program aimed to identify the health status of Mergan’s people through health screening and to help them to maintain their health. This program was conducted in collaboration between the Faculty members and students of Pharmacy Faculty of Universitas Sanata Dharma Yogyakarta (USD). There were two consecutive periods; the first was in 7th of May and the second was in 22nd of October 2018. Health education, health screening, and health examination were conducted in each period. There were 93 people involved in the first period and 64 people in the second; however, only 32 persons who completely attended the two meeting periods. The program resulted data of 60.7% Mergan’s people with a risk of dyslipidemia, and 59.0% with hyperglycemic. There was no significant difference between the first and the second periods of examination of glucose level, cholesterol, and uric acid. Therefore, it is urgent to educate people in Mergan Village to promote and maintain a healthy lifestyle in order to decrease morbidity of degenerative disease in the community.